Enhancing English Language Acquisition for Youth: Effective Strategies in Second Language Education - Akramkhojayeva Rakhima Zakirzhanovna (Research Retrieval and Academic Letters, 2023)
This comprehensive article, authored by a master’s degree English teacher with extensive experience in teaching young learners for eight years, delves into the multifaceted domain of teaching English as a second language (ESL) to the youth demographic. Merging scholarly insights with practical expertise, this article meticulously examines a range of pedagogical methods that have proven to be efficacious in facilitating ESL acquisition. These methods include creating an immersive learning environment, implementing Communicative Language Teaching (CLT), integrating technology and multimedia, nurturing cultural sensitivity, personalizing learning experiences, fostering critical thinking, and deploying continuous assessment strategies. The synthesis of these approaches equips educators with a comprehensive tool kit to enhance the ESL learning journey for youth.